Differential response of RTGUTGC and RTGILL-W1 rainbow trout epithelial cell lines to viral stimulation - Simón, Rocío (Journal of fish diseases, 2023)
© 2023 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.